"Context-Specific" Teacher Preparation for New York City: An Exploration of the Content of Context in Bard College's Urban Teacher Residency Program. (December 2016) - Hammerness, Karen; Craig, Elizabeth
In this article, we examine a residency program that was developed to prepare teachers specifically for New York City schools—the Bard College Master of Arts in Teaching Urban Teacher Residency program. This focused preparation on the particular urban context of New York City provides us with a unique opportunity to examine the nature of preparation—how such targeted preparation is conceptualized and organized, what it offers, and what might be missing and need to be strengthened. We also describe the development of a yearlong course aimed at preparing teachers for New York, which emerged from this study.